The multifunctional role of the pallilysin‐associated Treponema pallidum protein, Tp0750, in promoting fibrinolysis and extracellular matrix component degradation. Issue 3 (7th January 2014) - Houston, Simon; Russell, Shannon; Hof, Rebecca; Roberts, Alanna K.; Cullen, Paul; Irvine, Kyle; Smith, Derek S.; Borchers, Christoph H.; Tonkin, Michelle L.; Boulanger, Martin J.; Cameron, Caroline E.
Summary The mechanisms that facilitate dissemination of the highly invasive spirochaete, Treponema pallidum, are incompletely understood. Previous studies showed the treponemal metalloprotease pallilysin (Tp0751) possesses fibrin clot degradation capability, suggesting a role in treponemal dissemination. In the current study we report characterization of the functionally linked protein Tp0750. Structural modelling predicts Tp0750 contains a von Willebrand factor type A (vWFA) domain, a protein‐protein interaction domain commonly observed in extracellular matrix (ECM)‐binding proteins. We report Tp0750 is a serine protease that degrades the major clot components fibrinogen and fibronectin. We also demonstrate Tp0750 cleaves a matrix metalloprotease (MMP) peptide substrate that is targeted by several MMPs, enzymes central to ECM remodelling. Through proteomic analyses we show Tp0750 binds the endothelial fibrinolytic receptor, annexin A2, in a specific and dose‐dependent manner. These results suggest Tp0750 constitutes a multifunctional protein that is able to (1) degrade infection‐limiting clots by both inhibiting clot formation through degradation of host coagulation cascade proteins and promoting clot dissolution by complexing with host proteins involved in the fibrinolytic cascade and (2) facilitate ECM degradation via MMP‐like proteolysis of host components. We propose that through these activities Tp0750 functions in concert with pallilysin to enable T. pallidum dissemination.